Keeping Them in Their Place: Migrant Women Workers in Spain’s Strawberry Industry - E. Mannon, Susan; Petrzelka, Peggy; M. Glass, Christy; Radel, Claudia (The International Journal of Sociology of Agriculture and Food, 2012)
The idea of guest-worker migration has resurfaced in recent decades as the global agri-food industry has confronted a shortage of workers willing to take low-wage and often seasonal jobs. To date, there have been very few cases studies of these twenty-first century guest-worker programs and their role in managing contemporary labor migration. This article examines guest-worker migration in the strawberry industry of southern Spain. In this case, guest-worker programs attempt to regulate and enforce the circular migration of foreign workers in Spain. By making future work contracts contingent on migrants’ return to their country of origin, by recruiting migrant workers from various countries, and by targeting women with dependent children, these programs help to discipline migrant workers into the rigors of circular migration. We argue that although the program has been lauded as a model of twenty-first century labor migration, it succeeds primarily by keeping foreign, low-wage, women workers ‘in their place’.